Perkembangan Konsep Keyakinan Dari Masa Bali Purba Sampai Kini - Ni Wayan Silawati (Purwadita : Jurnal Agama dan Budaya, 2019)
The funeral tradition with sarcophagus was carried out for years, later the next period pemakamam with sarcophagus replaced with Enao trees made like sarcophagus as a means to bury people who died, especially in the old village. Until now, many relics of the enao tree have been found as a means of burying the dead. Then the Spirit died at Puja near his house. The possibility of its evolution of worship of the ancestral Spirit was made a sanctified place, there was placed in the house room, there was a kind of Pelinggih. Other beliefs dismissed trust in ancestors, also trusted the power of nature, which was felt to be helpful in his life. So that you believe in natural forces such as: Water, big trees, mountains, lakes, seas and so on, so that Westerners sabotage the ancient people who believe in the forces of nature (Animism and Dynamism).